Serial viral load analysis by DDPCR to evaluate FNC efficacy and safety in the treatment of mild cases of COVID-19 - da Silva, Renato Martins; Gebe Abreu Cabral, Paula; de Souza, Sávio Bastos; Arruda, Raul Ferraz; Cabral, Sheila Passos de Figueiredo; de Assis, Arícia Leone Evangelista Monteiro; Martins, Yolanda Porto Muniz; Tavares, Carlos Augusto de Araújo; Viana Junior, Antônio Brazil; Chang, Junbiao; Lei, Pingsheng (Frontiers in Medicine, 2023)
Introduction: The SARS-CoV-2 outbreak has threatened the human population globally as the numbers of reinfection cases even after large-scale vaccination. Trials have been carried out to find drugs effective in fighting the disease, as COVID-19 is being considered a treatable disease only after we have antivirals. A clinical candidate originally developed for HIV treatment, AZVUDINE (FNC), is a promising drug in the treatment of COVID-19. Methods: To predict the clinical outcome of COVID-19, we examined the course of viral load, every 48hs, by RT-PCR, and disease severity using an antiviral drug, FNC, with 281 participants. A randomized clinical trial was performed to evaluate the efficacy of FNC added to standard treatment, compared with placebo group added to standard treatment, for patients with mild COVID-19. RT-qPCR and ddPCR were applied to estimate the viral load in samples from patients. Also, the clinical improvement was evaluated as well as the liver and kidney function. Results and Discussion: Notably, the FNC treatment in the mild COVID-19 patients may shorten the time of the nucleic acid negative conversion (NANC) versus placebo group. In addition, the FNC was effective in reducing the viral load of these participants. The present clinical trial results showed that the FNC accelerate the elimination of the virus in and could reduce treatment time of mild patients and save a lot of medical resources, making it a strong candidate for the outpatient and home treatment of COVID-19. Funding: This study was funded by HRH. Trial registration number: NCT05033145 https://clinicaltrials.gov/ct2/show/NCT05033145